2017
DOI: 10.1007/s10549-017-4612-y
|View full text |Cite
|
Sign up to set email alerts
|

Potential biomarkers of CDK4/6 inhibitors in hormone receptor-positive advanced breast cancer

Abstract: We have found that although CDK4/6 inhibitors combined with endocrine therapy were potent, the toxicity and financial burden also increased. To maximize the effect of the combinations and select patients that best response to such combinations, further experiments and trials are expected to confirm these molecules as reliable biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…1E and F). Given the role of CCNE1 in inducing E2F transcription factor and cell proliferation, these data support a mechanism of resistance to ET and CDK4/6 inhibitors, as described previously (31)(32)(33).…”
Section: Response By Baseline Clinical Pathologic and Molecular Chasupporting
confidence: 85%
“…1E and F). Given the role of CCNE1 in inducing E2F transcription factor and cell proliferation, these data support a mechanism of resistance to ET and CDK4/6 inhibitors, as described previously (31)(32)(33).…”
Section: Response By Baseline Clinical Pathologic and Molecular Chasupporting
confidence: 85%
“…While several of these have been reported not to predict differential benefit from the addition of CDK4/6 inhibitor, a recent report from the PALOMA-3 trial demonstrated relatively less benefit in cyclin E overexpressing (CCNE1 mRNA) tumors when palbociclib was added to fulvestrant, supporting the idea that Cyclin E-CDK2 represents a major bypass mechanism for CDK4/6 inhibitors [47]. While current clinical use of CDK4/6 inhibitors is based solely on ER+/HER2-status, investigation of biomarkers predictive of CDK4/6 inhibitor response, beyond ER-positivity, is an ongoing, essential area of research [45].…”
Section: Targeting the Cell Cycle In Er+ Breast Cancer: Cdk4/6 Inhibimentioning
confidence: 94%
“…Other candidate predictive biomarkers that have been considered or included in various studies include Ki67 levels; expression of p16, CDK4, CDK6, Cyclin E, Cdk2 and Rb; hormone-receptor status; as well as specific mutations (e.g. PIK3CA, ESR1, and TP53) [45,46]. While several of these have been reported not to predict differential benefit from the addition of CDK4/6 inhibitor, a recent report from the PALOMA-3 trial demonstrated relatively less benefit in cyclin E overexpressing (CCNE1 mRNA) tumors when palbociclib was added to fulvestrant, supporting the idea that Cyclin E-CDK2 represents a major bypass mechanism for CDK4/6 inhibitors [47].…”
Section: Targeting the Cell Cycle In Er+ Breast Cancer: Cdk4/6 Inhibimentioning
confidence: 99%
“…ESR1 phosphorylation further increases its affinity for ERE [501]. In the nucleus, it activates estrogen responsive genes including TP53 [502], BRCA1 [503], CDK4/6 [504], as well as many others [505][506][507][508][509]. These genes promote cellular proliferation and survival [506].…”
Section: Classificationmentioning
confidence: 99%